The Effect of HSSC Program to Improve Communication Skill on Kindergarten Students - Musawwir, Musawwir; Thalib, Tarmizi; Zubair, Arie Gunawan Hazairin; Thalib, Syamsul Bachri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The study aimed to discover the extent of the influence of Head Start on the Science and Communication Program on communication ability applied to kindergarten students at TK. Bawakaraeng in Makassar by employing the HSSC module, which passed the process of validation by the experts. The study employed an intervention that focused on the active role of parents and teachers in the learning process. Moreover, the material used was a science project method aimed at motivating students to be more active in the learning process. The approach and type of the study employed experiment research with one group pretest-posttest model where pretest was conducted before the intervention was given and posttest after the intervention was given. The subjects of the study were 15 students based on the set criteria. Data were collected through direct observation and evaluated the communication ability based on the communication scale, which was validated beforehand. The communication ability scale was formulated based on indicators: the ability to memorize, comprehension and information, ability to connect, ability to conduct simple analysis, and ability to assess. Data were analyzed by employing Wilcoxon analysis, used in a study using a non-parametric approach. The study's result revealed significant changes in the communication ability of kindergarten students of TK. Bawakaraeng indicated by the result of Wilcoxon analysis by -3.411. The score was appropriate with the convention of the result of data analysis which was greater than 0.5 (α > 0.5). Based on the indicators, the result also showed significant changes indicated by significant improvement between the scores before and after the intervention. The study concluded that the HSSC program's utilization in the project method learning process could improve the students' communication ability.